Short-term Increase in Risk of Overweight and Concomitant Systolic Blood Pressure Elevation in Treatment-Naïve Persons Starting INSTI-Based Antiretroviral Therapy. (13th November 2019) - Galdamez, Ronald; García, José A; Fernández, Marta; Robledano, Catalina; Agulló, Vanessa; García-Abellán, Javier; Telenti, Guillermo; Padilla, Sergio; Gutiérrez, Félix; Masiá, Mar
Abstract: Objective: Integrase strand transfer inhibitors (INSTI) have been associated with weight gain, but their effect on short-term overweight and obesity incidence, blood pressure (BP), and metabolic markers has not been described in treatment-naïve people with HIV(PWH). Method: Medical records of treatment-naïve persons starting antiretroviral therapy (ART) at the HIV Clinic of University Hospital of Elche, Spain, between January 2007 and July 2019 were reviewed retrospectively. Standard procedures included measurements of weight, BP, and metabolic assessment. Data at baseline, 48, 72, and 96 weeks post ART initiation were analyzed. We used Cox mixed-effects model to generate predictions of body mass index (BMI) over time and generalized additive mixed models to relax the linearity assumptions and generate 95% confidence intervals in the multivariable adjustment. Results: Among 219 (median age, 44.0 years; interquartile range [IQR], 37.0–53.5; 46 females) participants. Baseline weight mean (standard deviation) was 70.4 (13.7) kg without difference between regimens; 66% had a BMI <25 kg/mt 2 . The incidence of overweight and obesity was significantly greater in persons starting INSTI-based regimens: 15 (36.6%) of 41 patients treated with INSTI versus 30 (28.9%) of 104 treated with other ART regimens (hazard ratio, 2.3; 95% CI, 1.2–4.4; P = .011). In contrast to other ART regimens, patients treated with INSTI showed a significant increase in systolic BP (SBP) (adjusted increase, 7.0 mmHg; 95% CI, 0.3–13.7; P = .039) that was correlated with weight gain ( r = 0.13; 95% CI, 0.10–0.16; P < .001). Patients who reached overweight and obesity in INSTI-based ART showed a significant increase in LDL cholesterol. Conclusions: Integrase strand transfer inhibitors-based ART was associated in the short-term with a greater risk of overweight and obesity and SBP elevation. Patients developing overweight and obesity increased low-density lipoprotein cholesterol with no other metabolic disturbances.